The social context of quartz use - territories and on-site behaviour (Scottish Historical and Archaeological Internet Reports, 2008)
This section deals with the social context of quartz use in Scotland. In prehistory, quartz production was an element of active societies, and an attempt is made to use the available Scottish quartz assemblages to provide information on aspects of these societies.